2015
DOI: 10.1007/s12035-015-9442-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Capability of Human Bone Marrow Mesenchymal Stem Cells and Endometrial Stem Cells to Differentiate into Motor Neurons on Electrospun Poly(ε-caprolactone) Scaffold

Abstract: Human endometrial and bone marrow-derived mesenchymal stem cells can be differentiated into a number of cell lineages. Mesenchymal stem cells (MSCs) are potential candidates for cellular therapy. The differentiation of human bone marrow MSCs (hBM-MSCs) and endometrial stem cells (hEnSCs) into motor neuron-like cells has been rarely investigated previously; however, the comparison between these stem cells when they are differentiated into motor neuron-like cell is yet to be studied. The aim of this study was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Suitable cells for tissue engineering should be easily cultured and adhere . Flow cytometry analyses of these cells showed that CD73, CD105, CD29, CD44, and CD90 were highly expressed in BM‐MSCs while the expression of BM‐MSCs surface antigens, such as CD45 and CD34, were extremely low.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Suitable cells for tissue engineering should be easily cultured and adhere . Flow cytometry analyses of these cells showed that CD73, CD105, CD29, CD44, and CD90 were highly expressed in BM‐MSCs while the expression of BM‐MSCs surface antigens, such as CD45 and CD34, were extremely low.…”
Section: Discussionmentioning
confidence: 80%
“…They have been in the spotlight of the regenerative medicine because of their various remarkable properties, such as self‐renewal ability, immunomodulatory properties, strong secretory properties, and their ability to differentiate into various epidermal cell types, such as keratinocytes and fibroblasts as well as dermal appendixes including, apocrine glands or hair follicle. It has also been reported that increase in basic fibroblast growth factor (b‐FGF), epidermal growth factor (EGF), and vascular endothelial growth factor (VEGF) levels are induced by MSCs . Local transplantation of rat adipose‐derived MSCs to an excisional wound‐healing model revealed enhanced granulation tissue deposition and epithelialization …”
Section: Introductionmentioning
confidence: 99%
“…Stem cells may be extracted from different origins, like adipose tissue, bone marrow, muscle, periosteum, and placenta (26)(27)(28)(29). Endometrial stem cells are in fact a group of stem cells (adult stem cell), which are extracted from endometrial tissue of the uterus, which present some features similar to mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured endometrial MSCs usually express typical BM-MSC markers, such as CD90, CD105, CD146 28 , CD9, CD13, CD14, CD29, CD31, CD44, CD73, CD117 and CD133 18 , but they do not express other markers, such as STRO 1, CD31 (typical of endothelial origin cells), or CD34, from haematopoietic stem cells (HSCs) and endothelial cells. 29 General adult stem cell markers, such as bcl-2, c-kit (CD117) and CD34, have been identified in human endometrial tissue.…”
Section: Endometrium Stem Cell Phenotypementioning
confidence: 99%
“…28,92,93 Therefore, these cells might be used to treat affections such as cardiac disease, muscle degeneration, diabetes type 1 and neurodegenerative diseases in the future.…”
Section: Endometrium As a Source Of Mesenchymal Stem Cellsmentioning
confidence: 99%